Exploring Science Teacher Prospective Misconception in Hydrocarbon: a Diagnostic Three Tiers Test - Hayati, Muriani Nur; Riyanta, Aldi Budi (Unnes Science Education Journal, 2025)
Chemistry learning is considered a difficult and complex subject for some students and prospective science teachers. For this reason, it is necessary to know the understanding related to chemistry learning, especially on hydrocarbon materials so as not to cause misconceptions. The aim of this research is to identify organic chemistry misconceptions among prospective science teacher students regarding hydrocarbon material, namely the characteristics of hydrocarbons and isomers of chemical compounds. This research approach was qualitative using descriptive analyze combined with systematic literarature review and bibliometric. Determining misconceptions using a modified three tiers diagnostic test.  The research subjects were 12 students and the questions tested were 10 essay questions. The results of the research showed that high misconceptions (81.2%)  regarding naming, chemical reactions,  isomers, and chirality, highlighting the prevalence of misconceptions in basic concepts. This research emphasizes the importance of good concept understanding to prevent misconceptions among prospective science teachers.